A systematic inspection into the criteria of lecturer performance in educational domain - Al-Masri O.H.; Drus S.M.; Aldalaien A.A.A.-H. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
This paper is to survey researchers efforts in response to the most number of criteria of lecturers performance into various domains, connecting the research insights from the literature into a consistent taxonomy, and figuring out the gaps on this vital research area. The fundamental search is relating to 1) personnel evalaution especially lecturer; 2) education-related; 3) criteria and applications (methods). Web of Science, ScienceDirect, and IEEE Xplore are reliable sources that can cover education and technical literature. The final number of studies is 78. Five articles are reviews to characterize the evaluation criteria for specific specializations. An another group (73/78) is research articles that include diverse evaluation criteria and domains. Most domains covered criteria, such as knowledge, skills, experience, and qualification. BEIESP.